1971
DOI: 10.1152/ajplegacy.1971.221.1.376
|View full text |Cite
|
Sign up to set email alerts
|

Rat pancreatic hydrolases from birth to weaning and dietary adaptation after weaning

Abstract: Rat pancreatic hydrolases from birth to weaning and dietary adaptation cfter weaning. Am. J. Physi~l. 221(l): 376-381. 197 1 .-Within 2-4 days after birth, there was a marked depletion of cr-amylase and chymotrypsinogen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
54
1
3

Year Published

1979
1979
1990
1990

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(64 citation statements)
references
References 0 publications
6
54
1
3
Order By: Relevance
“…Lipase activity induction was nevertheless much lower than the 6-fold increase found in 21-day-old rats (25-28 g) fed lard diets (IOYO vegetable oil, 400/0 animal fat) for 4 days [12,251. The fact that weaning rats were used in the latter case (21-day-old animals) could explain the observed discrepancies between these two studies.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Lipase activity induction was nevertheless much lower than the 6-fold increase found in 21-day-old rats (25-28 g) fed lard diets (IOYO vegetable oil, 400/0 animal fat) for 4 days [12,251. The fact that weaning rats were used in the latter case (21-day-old animals) could explain the observed discrepancies between these two studies.…”
Section: Discussionmentioning
confidence: 64%
“…Although the causal mechanisms still remain elusive, recent animal experiments suggested that secretion might play a major part in this adaptation since ingestion of fat resulted in the release of secretin [7 -91. Furthermore, the adaptative response patterns of pancreatic enzymes to dietary fat [I] and secretin [lo, 111 were found to be similar.Pancreatic lipase adaptation is a rapid process since a fourfold increase in the enzyme specific activity could be measured in the pancreas of just-weaned rats after the ingestion of a lard-rich diet for two days only [12]. The most significant adjustment in lipase specific activity, a six-fold increase as compared with control rat, occurred after the fourth day.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Les travaux réalisés depuis près de 40 années ont fourni un certain nombre de données qui sont à l'origine de quelques hypothèses. Il semble que l'on peut aujourd'hui retenir l'idée du rôle joué par les produits d'hydrolyse digestive des constituants alimentaires de la ration (Ben Abdeljlil, Visani et Desnuelle,1963 ;Robberecht et al, 1971 ;Felber, Zermatten et Dick, 1974 ;Johnson, Hurwitz et Kretchmer, 1977 ;Corring, 1977). Ainsi, on sait que l'activité de l'amylase pancréatique n'est pas modifiée lorsqu'on substitue dans le régime alimentaire l'amidon par du glucose (Ben Abdeljlil, Visani et Desnuelle, 1963 ;Robberecht et al, 1971) Yudkin, 1963 ;Deschodt-Lanckman et al, 1971 ; Simoes Nunes et Corring, 1979).…”
Section: Introductionunclassified
“…Introduction -De nombreux travaux ont mis en évidence un effet de l'âge et du sevrage sur les activités des protéases pancréatiques chez plusieurs espèces animales (Guilloteau et al, 1983;Robberecht et al, 1971 Chez le rat, le niveau de ces hydrolases au cours du développement dépend de celui de leurs ARN messagers (ARNm) spécifiques (Han et al, 1986 (Bundy, 1963 …”
unclassified